2018
DOI: 10.1016/j.clinph.2018.03.013
|View full text |Cite
|
Sign up to set email alerts
|

Quantitative electroencephalography as a marker of cognitive fluctuations in dementia with Lewy bodies and an aid to differential diagnosis

Abstract: HighlightsEEG slowing was evident in dementia with Lewy bodies (DLB) and Parkinson’s disease dementia (PDD) and less in Alzheimer’s disease (AD) patients compared to controls.Dominant rhythm variability was larger in AD but only correlated with cognitive fluctuations in DLB.QEEG variables classified DLB and AD patients with high sensitivity and specificity.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

10
62
3

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 49 publications
(75 citation statements)
references
References 61 publications
10
62
3
Order By: Relevance
“…We decided to use individual alpha peak frequencies to determine alpha power instead of using a fixed alpha frequency band (usually from 8 to 12 Hz) [21,22]. This was done to account for a shift of the alpha peak to slower frequencies in AD and LBD [26,27]. The mean alpha peak in the LBD group therefore lies within a frequency range that has been termed pre-alpha [41,42], but is also considered to represent the fast-theta band in other studies [27].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…We decided to use individual alpha peak frequencies to determine alpha power instead of using a fixed alpha frequency band (usually from 8 to 12 Hz) [21,22]. This was done to account for a shift of the alpha peak to slower frequencies in AD and LBD [26,27]. The mean alpha peak in the LBD group therefore lies within a frequency range that has been termed pre-alpha [41,42], but is also considered to represent the fast-theta band in other studies [27].…”
Section: Discussionmentioning
confidence: 99%
“…Individual alpha peak frequencies were calculated by finding the peak in the PSD in the extended alpha frequency band from 4 to 14 Hz [20] using the eyes-closed data. Individual alpha peak frequencies were used instead of the standard alpha frequency band to account for a shift of the alpha peak to slower frequencies in AD and LBD [26,27].…”
Section: Alpha Reactivity Analysismentioning
confidence: 99%
“…In particular, previous studies focused on the shifting of the dominant frequency (DF) towards slower frequencies. These studies showed that the frequency with the most prominent peak in the power spectrum moves towards a lower range of frequencies in patients when compared with healthy controls (Bonanni et al, ; Peraza et al, ; Stylianou et al, ). DLB related changes were also found by EEG network connectivity studies.…”
Section: Introductionmentioning
confidence: 99%
“…The overlapping causes and symptoms often lead scientists to consider these two diseases as a sole group when aiming to assess effective biomarkers for the diagnosis of dementia (Lippa et al, 2007). However, due to enhanced cognitive dysfunction preceding the motor symptoms in DLB pathology, as well as a greater accumulation of amyloid in DLB (Edison et al, 2008), physiological differences and biomarkers to differentiate DLB and PDD remain a research question and might provide further insight on the development of the two subtypes (Stylianou et al, 2018). Electroencephalography (EEG) is emerging as a convenient technique in dementia research.…”
mentioning
confidence: 99%
See 1 more Smart Citation